Analisis Pengaruh Upah Minimum, Tingkat Pendidikan dan Indeks Pembangunan Manusia (IPM) Terhadap Ketimpangan Pendapatan di Kabupaten Mimika - Salzabilah, Febi Yuni; Sambeko, Sartika Somoy Tangdo’; Hafifa, Arini Indah Nur; Nifanngeljau, Johanis (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2025)
The purpose of this study was to determine the effect of minimum wages, education levels and human development index (HDI) on income inequality in Mimika Regency. The data used is secondary data, the data collection technique used in this study is documentation sourced from BPS for the 2015-2021 period. The data analysis technique used in this study is multiple linear regression analysis, which is assisted by using SPSS 26 Software. The results found in this study are that the human development index has no effect and is not significant on income inequality (Gini Ratio), the unemployment rate has no effect and is not significant on income inequality (Gini Ratio) and the minimum wage of the Regency has a significant effect on income inequality (Gini Ratio) in the Regency in Mimika Regency.